Torção testicular tipo extravaginal em recém-nascido: Relato do diagnóstico em sala de parto - Dario Silva da Silva Júnior; Victor Santos de Melo; Aline Barbosa Lopes; Renato Pereira da Rocha; Virgílio Ribeiro Guedes (Sociedade Brasileira de Pediatria, 2022)
OBJECTIVE: To report a case of intrauterine testicular torsion diagnosed from the physical examination performed in the delivery room. CASE REPORT: Male newborn patient, natural birth. During the initial physical examination in the delivery room, the skin of the scrotum on the right was found to be slightly hyperchromic and more retracted, increased testicular volume on the right compared to the contralateral and hardened consistency, raising the diagnostic hypothesis of intrauterine torsion or testicular neoplasm. Ultrasonographic evaluation with color Doppler showed enlarged right testis, hyperechoic image suggestive of spermatic cord node and absence of blood flow signs within it. The newborn underwent surgical exploration with intraoperative finding of a necrotic testis, with subsequent orchiectomy and contralateral testis orchidopexy. Laboratory screening did not suggest testicular neoplasia. The anatomical specimen was sent for histopathological examination, which contains findings compatible with testicular torsion with absence of malignancy. CONCLUSIONS: Neonatal testicular torsion is a rare condition, but it is important to know this condition in order to be able to detect it during the physical examination of a newborn. Testicular torsion occurs when the spermatic cord twists on its own axis, which can lead to an ischemic infarction of the testis. Once the diagnosis is confirmed, a surgical exploration aims at the detortion of the testicle or its removal if this is not feasible, and may be considered an exploration and correction of the contralateral testicle as a prophylactic way of future torsion.